2022
DOI: 10.1128/msystems.01393-21
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics and Transcriptomics Uncover Key Processes for Elasnin Tolerance in Methicillin-Resistant Staphylococcus aureus

Abstract: Besides the excellent antibiofilm properties of elasnin, we discovered that it can also kill growing methicillin-resistant Staphylococcus aureus (MRSA) planktonic cells. We subjected MRSA cells to an in vitro evolution experiment, and the resulting evolved strains exhibited increased elasnin tolerance, reduced growth rate, loss of pigmentation, an increased proportion of small-colony formation, and they became more sensitive toward daptomycin and lysostaphin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Therefore, we were interested in seeing how elasnin affects a daptomycin-resistant MRSA (DAP R ) strain, which has membrane and cell-wall modifications due to the mutation it possessed (T345A gain-of-function in the mprF gene), and also lower biofilm formation compared to the WT strain ( 16 ). Our recent transcriptomic study has also shown that elasnin treatment led to a 10-fold downregulation in the expression of mprF gene on MRSA planktonic cells, the gene that was mutated in the DAP R strain ( 8 ).…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Therefore, we were interested in seeing how elasnin affects a daptomycin-resistant MRSA (DAP R ) strain, which has membrane and cell-wall modifications due to the mutation it possessed (T345A gain-of-function in the mprF gene), and also lower biofilm formation compared to the WT strain ( 16 ). Our recent transcriptomic study has also shown that elasnin treatment led to a 10-fold downregulation in the expression of mprF gene on MRSA planktonic cells, the gene that was mutated in the DAP R strain ( 8 ).…”
Section: Resultsmentioning
confidence: 89%
“…It was reported that elasnin interfered with cell division and cell wall biosynthesis in both planktonic culture and biofilms ( 7 , 8 ). Therefore, we were interested in seeing how elasnin affects a daptomycin-resistant MRSA (DAP R ) strain, which has membrane and cell-wall modifications due to the mutation it possessed (T345A gain-of-function in the mprF gene), and also lower biofilm formation compared to the WT strain ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations